The emergence of entrepreneurial economics - Vinig, G. T.; Van der Voort, R. C. W.; Burgelman, Robert A.; Chesbrough, Henry William (Research on technological innovation, management and policy, 2005)
If entrepreneurship remains as important to the economy as ever, then the continuing failure of mainstream economics to adequately account for entrepreneurship indicates that fundamental principles require re-evaluation. It seems no longer possible to expect that only theoretical refinements and extending known principles can provide for a theory of entrepreneurship. The articles in this book provide interesting new ideas and insights on a theory of entrepreneurship in the economy (W.J. Baumol, D.B. Audretsch, A.V. Bhide) in part one, and interesting recent research on entrepreneurship in part two. In his article, A. Heertje writes that: It is interesting to note that in the aftermath of the Schumpeter revival, since the eighties of last century our field observes the emergence of entrepreneurial economics. Several threads come together. Economic theory substituted the paradigm of perfect knowledge for imperfect information, developed a more refined analysis of risk and uncertainty in economic life and the theory of games provided the framework for the analysis of strategic behaviour in general. The theory of industrial organisation entered a higher level of sophistication and chaos theory as part of economic dynamics helped to transform verbal Schumpeterian ideas and intuitions into a refined mathematical structure. Also, the application of insights from theoretical physics, like thermodynamics and entropy are very promising. These developments have brought the modern entrepreneur of flesh and blood, being embedded in a global world of enduring technical change, uncertain challenges, threats and opportunities in the forefront of advanced economic analysis. We do hope that this book contributes to the emergence of the Entrepreneurial Economics field, or school of thought, in which the study of patterns in the complex, seemingly chaotic and unpredictable process of entrepreneurship and its role in the economy stands central.